DAMPAK BELT AND ROAD INITIATIVE (BRI) TIONGKOK TERHADAP PEMBANGUNAN INFRASTRUKTUR DAN PARIWISATA FILIPINA - Ester Mahdalena Nainggolan; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Began in 2010 in the term of Benigno Aquino’s Presidency the bilateral relations between Phillipines and China was distantly spaced. However, this condition was changed as Rodrigo Duterte was chosen as Presdent in May 2016. In October 2016, President Rodrigo Duterte decided to run intensive relations with China and joined the Belt and Road Initiative (BRI). Therefore, this study was conducted to explain the influence of the Philippines joining the BRI policy. In order to fulfil the above purpose, this study used the perspective of liberalism and the nation-state analysis level and was explored through interdependence theory; Furthermore, this research was a library reseach using documentary data analysis taken from official websites, journals and news online websites.This research shows that the collaboration between the Philippines and China through BRI can improve the Philippine economy through an increase in infrastructure development in the Philippines. From the tourism sector there is an increase in the number of foreign tourists visiting the Philippines, especially from Cina. On the other hand, the Philippine’s export to China has increased significantly, although its percentage from year-to-year trade is quite fluctuating. Keywords: Belt and Road Initiative (BRI), Infrastructure, Export, Tourism